Incisional Negative Pressure Wound Therapy devices applied after Total Ankle Arthroplasty: A Hospital-Based Health Technology Assessment - Jamal Atfeh; Pascale Guerre; Emmanuelle Carre; Jean-Luc Besse; Laure Huot (PLoS ONE, 2025)
Introduction A portable, single-use incisional Negative Pressure Wound Therapy (iNPWT) device could be used directly on the wound incision following Total Ankle Arthroplasty (TAA). In order to support local decision-making in a French university hospital for the adoption of such device in this indication, a three-dimensional (clinical, economic and organizational) Hospital Based-Health Technology Assessment (HB-HTA) was conducted. Materials and methods The HB-HTA was based on: a literature review; results from the PICO-PTC single-site randomized controlled trial (ClinicalTrial.gov identifier NCT03886818); and semi-structured interviews with healthcare professionals. Results Two comparative retrospective cohort studies were retrieved from the literature review. They suggested a decreased incidence of wound healing complications with iNPWT compared to standard dressings, although no difference was found in the PICO-PTC study. There was no significant difference in the PICO-PTC study on Medicine-Surgery-Obstetrics hospital costs between the two strategies: €10,639.65 [CI 95% (7,997.45; 17,988.68)] in the iNPWT group versus €9,672.59 [CI 95% (7,966.29; 13,393.65)] in the standard dressings group. Adoption of this prophylactic strategy would result in an approval to pay a 1.5% supplement to the Medicine-Surgery-Obstetrics hospitalization costs. It could also improve professionals’ workflow, and facilitate wound healing monitoring for nurses in orthopedic departments compared to standard dressings. Conclusion The clinical effectiveness of the iNPWT single-use portable device could not be demonstrated compared to standard dressings for prophylactic use, in terms of the incidence of wound healing complications, in patients scheduled for TAA and not selected on the basis of risk factors. However, as this strategy may bring organizational benefits and has not been associated with significant economic costs, the adoption of iNPWT in orthopedic departments could be made according to the surgeon’s clinical expertise, based for instance on the patient’s risk factors for complications.